Analisis Pengaruh Relative Advantage, Complexity, Observability dan Trialability terhadap Niat Adopsi Cloud Accounting di Jabodetabek - Moch. Arridho Pramudana; Erliana Banjarnahor (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the influence of relative advantage, complexity, observability, and trialability on the intention to adopt cloud accounting in Jabodetabek. A quantitative approach was employed, with a survey as the data collection instrument. The research variables were measured using a Likert scale. The sampling method applied in this study was purposive sampling. Primary data were collected through questionnaires distributed via Google Forms, using social media platforms such as WhatsApp, LinkedIn, Twitter, and Kudata. Data analysis included descriptive statistical tests, validity, reliability, classical assumption tests, and hypothesis testing. The findings indicate that relative advantage, trialability, and observability positively influence the intention to adopt cloud accounting, whereas complexity does not significantly affect adoption intention. This study highlights the importance of cloud accounting as a technological innovation that can enhance the efficiency and effectiveness of accounting staff. Additionally, accounting professionals can adapt to dynamic technological innovations by investing in cloud accounting, which has high industrial value potential. The use of cloud accounting also facilitates better management of tasks for accounting staff.